2009
DOI: 10.1890/09-0069.1
|View full text |Cite
|
Sign up to set email alerts
|

Plant species richness and functional composition drive overyielding in a six‐year grassland experiment

Abstract: Abstract. Plant diversity has been shown to increase community biomass in experimental communities, but the mechanisms resulting in such positive biodiversity effects have remained largely unknown. We used a large-scale six-year biodiversity experiment near Jena, Germany, to examine how aboveground community biomass in grasslands is affected by different components of plant diversity and thereby infer the mechanisms that may underlie positive biodiversity effects. As components of diversity we defined the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
371
5
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 361 publications
(416 citation statements)
references
References 69 publications
37
371
5
3
Order By: Relevance
“…Over the last decade, the search to find the underlying mechanisms of complementarity has often focussed on nutrients (mainly nitrogen) (e.g., Balvanera et al, 2006, Di Falco, 2012, Fargione et al, 2007 as well as -although to a lesser extent -on light (Hautier et al, 2009, Spehn et al, 2000 and water use (Caldeira et al, 2001, De Boeck et al, 2006. Also in the Jena Experiment, nitrogen and light use (Bessler et al, 2012, Gubsch et al, 2011, Roscher et al, 2011a have been reported to contribute to the overall complementarity effect (Marquard et al, 2009). The high N uptake in diverse mixtures thus not only led to higher aboveground productivity, but also to higher nitrogen pools with diversity (Oelmann et al 2011).…”
Section: Species Diversity and Grassland System Stabilitymentioning
confidence: 96%
See 4 more Smart Citations
“…Over the last decade, the search to find the underlying mechanisms of complementarity has often focussed on nutrients (mainly nitrogen) (e.g., Balvanera et al, 2006, Di Falco, 2012, Fargione et al, 2007 as well as -although to a lesser extent -on light (Hautier et al, 2009, Spehn et al, 2000 and water use (Caldeira et al, 2001, De Boeck et al, 2006. Also in the Jena Experiment, nitrogen and light use (Bessler et al, 2012, Gubsch et al, 2011, Roscher et al, 2011a have been reported to contribute to the overall complementarity effect (Marquard et al, 2009). The high N uptake in diverse mixtures thus not only led to higher aboveground productivity, but also to higher nitrogen pools with diversity (Oelmann et al 2011).…”
Section: Species Diversity and Grassland System Stabilitymentioning
confidence: 96%
“…Data further suggested that the main driving force behind such facilitative interactions in plots containing legumes was reduced competition for soil nitrate. Consequently, the presence of legumes (as well as tall herbs) had a strong positive effect on annual yield production (Marquard et al, 2009). However, despite clear evidence of facilitation by legumes in many studies, the wide-spread relationship between species diversity and productivity is not dominantly driven by legumes, as convincingly shown by van Ruijven and Berendse (2003) in a biodiversity study without any legume species.…”
Section: Species Diversity and Grassland System Stabilitymentioning
confidence: 99%
See 3 more Smart Citations